Anatomi dan Fisiologi Ginjal: Tinjauan Pustaka - Alwiyah, Fadilah; Rudiyanto, Waluyo; Anggraini, Dwi Indria; Windarti, Indri (CV. Jasa Sukses Abadi, 2024)
The kidneys are retroperitoneal organs located at the top on both sides of the III lumbar vertebra and attached directly to the abdominal or ventral wall of the M. psoas major and M. quadratus lumborum. The kidneys function to regulate the amount and concentration of ECF electrolytes and maintain nerve and muscle excitability, activating vitamin D which is important for calcium absorption in the digestive tract and producing erythropoietin which is a hormone to stimulate the bone marrow to form red blood cells. The main function of the kidneys is to filter and excrete metabolic waste products in the urine so that administration of toxic compounds or irritating compounds can cause degenerative changes such as fatty degeneration to necrosis of the kidneys. Disorders of the kidneys can disrupt kidney function. Chronic Kidney Disease (CKD) sufferers have several complications such as overhydration, hyperkalemia, metabolic acidosis, mineral and bone disorders, hypertension, anemia and dyslipidemia. The most common etiologies of CKD in adult patients are diabetes mellitus and hypertension. In children, the most common primary cause of PGTA is congenital abnormalities of the kidneys and urinary tract (such as obstructive uropathy, vesicoureteral reflux, renal dysplasia). Indonesian Nephrology Association (PERNEFRI) in 2006, which found that the prevalence of Chronic Kidney Disease (CKD) was 12.5%. Meanwhile, data according to the 2019 Health Insurance Administration (BPJS) shows that there were 1.93 million cases of kidney failure and 1.79 million cases in 2020. With this data, the author is interested in discussing the kidneys in more depth.